Toward achieving zero-emissions in European Union countries: The contributions of trade and overseas direct investments in consumption-based carbon emissions - Osarumwense Osabuohien-Irabor; Igor M. Drapkin (AIMS Environmental Science, 2023)
To achieve the ideal emissions reduction goals, several studies have suggested that carbon emissions should be examined in the framework of both territorial and consumption-based emissions. Nevertheless, the European Union (EU) SDGs targets aimed at mitigating carbon emissions based on the United Nation (UN) Kyoto Protocol structure, only appears to be concerned with the reduction of territorial-based emissions whilst emissions embodied on imported goods and services receive very little attention. To this end, this study examines the contributions of outward foreign direct investment (OFDI) and disaggregate trade flows toward consumption-based sustainability in twenty-one (21) EU countries for the period 1995–2019. The study utilizes the STIRPAT model (Stochastic Impacts by Regression on Population, Affluence, and Technology) and battery of advanced econometric techniques such as the Cross-Sectional Autoregressive Distributed Lag (CS-ARDL), Common Correlated Effects (CCE) and the Cross-Sectional Distributed Lags (CS-DL) to examine the short-and long-run dynamics of OFDI and trade on consumption-based emissions. Finding reveals that EU exports and OFDI spillover reduces consumption-based emission, whilst import of goods and services promote emissions both in the short-run and long-run. This suggests that the progress report on carbon emissions reduction for most EU countries under the greenhouse gas accounting systems are merely carbon emissions outsourced to low-income countries whilst consumption-based emission continues to increase. These findings are robust to several econometric problems with set of policy implications provided for policymakers and governments to formulate more efficient strategies toward the mitigation of consumption-based carbon emissions among EU countries.